Examining the effects of electronic oral communication on customer brand loyalty in the context of African banking industry - Mandhlazi, L. (FMLIC - Conference Proceedings, 2024)
The purpose of the study was to analyse the effects of electronic oral communication on customer brand loyalty within the context of the South African banking industry. The motivation of the study was to examine the effects that influence electronic oral communication through brand engagement leading to consumer brand loyalty within the South African banking industry, especially the dominant banks. Two objectives were proposed in this study; firstly, to examine the relationship between electronic oral communication (EOC) and brand engagement (BE) among social media consumers within the South African banks, and secondly, to analyse the relationship between brand engagement and customer brand loyalty (CBL) among social media consumers within South African banks. Descriptive methods were used to conduct the study. Structural equation modelling was used to analyse the data. The study found electronic oral communication to have a significant relationship with brand engagement. Furthermore, brand engagement was found to have a significant relationship with customer brand loyalty. The brand managers of local banks would be able to develop suitable strategies on how to effectively enhance a constructive conversation with customers whilst reducing and respond to negative comments across social media platforms. Again, the brand managers of the South African retail banks could devise appropriate strategies that can promote loyalty among online consumers, thereby becoming brand ambassadors of the banking services in the retail banking industry. The study added new knowledge to the existing literature since new theoretical lenses could be developed pertaining to EOC, BE and CBL within the context of online South African retail banks.